Specification a model for study of perceived risk - Lirios, Cruz García; Nájera, Margarita Juárez; Aguayo, José Marcos Bustos; Vázquez, Francisco Rubén Sandoval; Campas, Celia Yaneth Quiroz (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Security have concern authorities and civil society during last years. Different society’s substrates have different perceptions on security. Present document explores reliability and validity of an instrument which measures security perception in bachelor’s students by reviewing seven dimensions: territorial, national, public (government), human, public (self-protection), private and internet. Accordingly, setting values and residual permitted to accept the null hypothesis significant relationship between the theoretical dimensions with respect to the weighted factors.